The flying carpet to Baghdad one woman's fight for two orphans of war - Jaber, Hala (Macmillan, 2009)
Zahra, age three, and Hawra, only a few months old, were the only survivors of a missile strike in Baghdad in 2003 that killed the rest of their family. In London, foreign correspondent Hala Jaber was preparing to head to Iraq to cover the emerging war. After ten years spent trying to conceive, Jaber and her husband had finally resigned themselves to a childless future. Now she intended to bury her grief in her work, with some unusually dangerous reporting. Once in Iraq, though, Jaber found herself drawn again and again to stories of mothers and children, a path that led her to an Iraqi children's hospital--and to Zahra and Hawra and their heart-wrenching story. Almost instantly Jaber became entwined in the lives of these girls, and in a struggle to advocate on their behalf that reveals far more about the human cost of war than any news bulletin ever could.--From publisher description.